Triflate-functionalized calix[6]arenes as versatile building-blocks: application to the synthesis of an inherently chiral Zn(ii) complex. Issue 6 (11th January 2016) - Zahim, Sara; Lavendomme, Roy; Reinaud, Olivia; Luhmer, Michel; Evano, Gwilherm; Jabin, Ivan
Abstract : The regioselective synthesis of two calix[6]arenes bearing triflate groups is described. These compounds constitute versatile molecular platforms that allow the elaboration of sophisticated calixarene-based systems selectively functionalized at the large and/or at the small rim. Abstract : Cavity-based metal complexes can find many applications notably in the fields of catalysis and biomimicry. In this context, it was shown that metal complexes of calix[6]arenes bearing three aza-coordinating arms at the small rim provide excellent structural models of the poly-imidazole sites found in the active site of many metallo-enzymes. All these N -donor ligands were synthesized from the 1, 3, 5-tris-methoxy- p-t Bu-calix[6]arene platform, which presents some limitations in terms of functionalization. Therefore, there is a need for the development of new calix[6]arene-based building-blocks selectively protected at the small rim. Herein we describe the regioselective one step synthesis of two calix[6]arenes decorated with triflate groups, i.e. X6 H4 Tf2 2 and X6 H3 Tf3 3, from the parent calix[6]arene X6 H6 1 . It is shown that the triflate groups can either act as protecting or deactivating groups, allowing the elaboration of sophisticated calixarene-based systems selectively functionalized at the large and/or at the small rim. In addition, X6 H3 Tf3 3 is functionalized on the A, B, and D rings and thus gives access to inherently chiral compounds, as demonstrated by the synthesis of a rare example of inherently chiral cavity-based metal complex.